Implementation of renewable technologies in the repair of automotive units - Mokrynskyi, Roman (Global Prosperity, 2025)
Abstract. This article considers the introduction of restorative technologies in the repair of automotive units as a response to the shortage of spare parts, the rise in logistics costs, and the need to conserve resources. The approach is based on the idea of transitioning from “repair as a patch” to a controlled technological process that returns the part to a state close to new, with predictable characteristics and quality control. The article pays special attention to the situation in Ukraine. Here, the aging of the car fleet and the growth of the share of imported used cars are shaping the demand for the restoration of expensive components and reducing equipment downtime. The technical part considers three main approaches: laser deposition (DED) to restore the desired shape and restore working surfaces, HVOF spraying as a replacement for traditional chrome plating, and polymer composites for the repair of body parts without heating. The properties of the resulting coatings and layers are described - their structure, adhesion strength to the base, porosity, hardness and wear resistance - and attention is drawn to possible problems, in particular, a decrease in fatigue strength due to thermal effects, and how this can be compensated for by final hardening. The economic part is then presented as a convenient model for car repair shops and motor transport companies: the price of new parts is compared with the costs of restoration, it is estimated when the equipment will pay for itself, and what benefits come from reducing equipment downtime. The environmental benefit of the LCA approach was shown: restoration of parts usually requires less material and energy, therefore it produces lower emissions. It is also described how to organize the work of the repair site: which units and parts should be repaired, how to prepare surfaces, how to perform non-destructive testing and how to document the results. Therefore, these developments can be taken as a basis for a technical task for improving and modernizing a car service, but on condition that trained employees and clear standardized procedures will create and guarantee quality and durability.